KONSEP IHYA’ AL-MAWAT MENURUT HUKUM EKONOMI SYARIAH (DALAM FIQH ISLAM) DITINJAU DARI UNDANG-UNDANG POKOK AGRARIA DAN UNDANG-UNDANG KEHUTANAN - Ahmad Syarbaini (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2022)
Ihya 'al-mawat is the cultivation of vacant land that has not been processed and is not owned by someone to be used as productive land, both as agricultural land and building buildings. The legal basis for ihya 'al-mawat is based on the hadith of the Prophet Muhammad s.a.w, the law (mustahab), other opinions say ja'iz. The ways of Ihya' al-Mawat are as follows: fertilizing, planting, making fences, and digging trenches. The fiqh scholars agree that the conditions for ihya 'al-mawat include: Islam, puberty, intelligence, people working, land to be cultivated, not belonging to others, and the cultivation process. The majority of scholars have different opinions that clearing vacant land is the cause of land ownership without being obliged to require a permit from the government. As the Basic Agrarian Law and Forestry Law, it must first refer to the guidelines of the Qur'an and Al-Hadith. Basic Agrarian and Forestry Laws made by the government. Because Indonesia is a nationalist country, the law used is the 1945 Constitution of the Republic of Indonesia, article 33 paragraph 3 as the Basic Agrarian Law in Indonesia.